Conflict management in the supermarket sector (Research, Society and Development, 2018)
The purpose of this case is to present a successful entrepreneurial and entrepreneurial history in which persistence, work and unity were key elements for success. The case study reports the boldness of a farmer and merchant who left the interior of a Brazilian state with the idea and willpower to win in the capital. In a general way, it addresses the stages that had to overcome, becoming a reference in the Brazilian market. Even though it has to go through successions, internal conflicts, crises in the country's economy, competition from national and multinational markets, changes in governments, the company continues to be a successful brand and a leader in retail direct sales. The methodology used for this case for teaching was Internet research, experiences with representatives, suppliers, former employees and local media. The management aspects presented in the case are: organizational culture, conflict management and leadership. Thus, this case study is recommended the disciplines: Organizational Culture, Strategic Planning and Leadership.